Unpacking the impact of older adults' home death on family care-givers' experiences of home. (March 2016) - Milligan, Christine; Turner, Mary; Blake, Susan; Brearley, Sarah; Seamark, David; Thomas, Carol; Wang, Xu; Payne, Sheila
Abstract: Public Health England (2013) survey data indicates that while the place of death is geographically uneven across England, given a choice, many older people nearing end of life would prefer to die at home. There is, however, a growing critique that policies designed to support home death fail to understand the needs and preferences of older people and the impact on family carers. Such policies also make assumption about within whose home the home death takes place. Hence, there are major gaps in our understanding of firstly, where and how care work undertaken by family members within domestic settings takes place; and secondly, how it can create tensions between home and care that fundamentally disrupt the physical and socio-emotional meaning of home for family carers, impacting on their sense of home post-death. This can have consequences for their own well-being. In this paper we draw on interview data from our 'Unpacking the Home' study to elicit an in-depth understanding of how facilitating a home death can create an ambiguity of place for family carers, where the issues faced by them in caring for a dying older person at home, and the home death itself, can fundamentally reshape the meaning and sense of home. Highlights: The study identifies the paradox of 'whose home' in relation to the home death. Disruptions to the meaning of home following a home death can result in that 'home' becoming a 'house' for carers. Carers need better support post-death, especially those still living in the home where death occurred.